1989
DOI: 10.1128/aac.33.2.256
|View full text |Cite
|
Sign up to set email alerts
|

Treatment failure of norfloxacin against Campylobacter pylori and chronic gastritis in patients with nonulcerative dyspepsia

Abstract: Several reports have been published to show the in vitro susceptibility of Campylobacter pylori to different classes of antibiotics, including fluoroquinolones. The purpose of this study was to describe the clinical effect of norfloxacin on eradication of C. pylori in patients with gastritis. Endoscopy was performed in 38 patients with symptoms of nonulcerative dyspepsia. Of these, 20 patients had a C. pylori-positive culture. From this group, 17 patients were treated with norfloxacin for 1 month. After therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…However, when tested as single agents in clinical studies, erythromycin (23), doxycycline (35), ofloxacin (5), ciprofloxacin (34), and norfloxacin (24) have not succeeded in eradicating H. pylori. Failure of therapy and relapse have been common.…”
Section: Resultsmentioning
confidence: 99%
“…However, when tested as single agents in clinical studies, erythromycin (23), doxycycline (35), ofloxacin (5), ciprofloxacin (34), and norfloxacin (24) have not succeeded in eradicating H. pylori. Failure of therapy and relapse have been common.…”
Section: Resultsmentioning
confidence: 99%
“…Strains resistant to ciprofloxacin, metronidazole, erythromycin, and tobramycin were isolated. The experiments failed to select organisms resistant to bismuth subsalicylate, furazolidone, or amoxicillin, although the MIC of amoxicillin was increased 4-to 16-fold. With the exception of erythromycin, organisms with the selected resistance were stable after at least three passages on antibacterial agent-free medium.…”
mentioning
confidence: 99%
“…The second major problem has been the emergence of resistant strains during singleagent treatment. The development of resistance has been reported during treatment with several quinolones (10,16 (6,10), and rifampin (10).…”
mentioning
confidence: 99%
“…Histological studies have demonstrated that gastritis can be cured after this organism is eradicated from the gastric mucosa (24,27). However, clinical therapy by a single antibiotic has not been successful (12,27,28,40,42). Instead, combinations of chemotherapeutic agents including bismuth salts have yielded better results (27,43).…”
mentioning
confidence: 99%